Diversidad de Géneros del Fitoplancton del embalse de Betania–Huila y su importancia como bioindicadores - Martinez-Silva, Paula; Delgado-Fonseca, Juan Felipe; Muñoz-Yustres, Jorge Leonardo (Revista Científica, 2016)
The Betania reservoir of water is one of the strategic ecosystems of the Huila department, being of vital importance not only for the generation of electricity but for the production of fish which is the main activity for the last thirty years. Nevertheless, activities such as pisiculture, the dumping of wastewater generated by agricultural activities, have diminished the quality of the water and accelerated the eutrophication process. In this research, phytoplankton samples were taken along one year with the objective to stablish through the use of bioindicators, such as microalgae, the actual state of this water body as well as the spatial – temporal variation of species and genres of algae amongst stations and samplings.